Development prospects of enterprises through electronic commerce. - Maydisarova, Динара; Jumabaeva, Акерке (Рroblems of engineering and professional education, 2023)
This article examines the current state of the Kazakhstani Internet space and the prospects for the development of e-commerce. Online store as an innovative way to promote domestic products and develop an enterprise.